2016
DOI: 10.7759/cureus.478
|View full text |Cite
|
Sign up to set email alerts
|

KDR Mutation as a Novel Predictive Biomarker of Exceptional Response to Regorafenib in Metastatic Colorectal Cancer

Abstract: This is the case of an 84-year-old woman diagnosed with Stage IVb colon adenocarcinoma (CRC) metastatic to the liver, retroperitoneum, anastomotic site, and distal rectal sigmoid colon. She experienced intolerable side effects to systemic chemotherapy with 5-fluorouracil and bevacizumab, as well as disease progression. Next generation sequencing of her tumor was ordered, and further discussion of her malignancy’s genomic information took place at a multidisciplinary molecular tumor board. The patient had mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…This difference might be present due to different cancer groups and the small number of patients studied. Furthermore, in a recently reported case study [15], KDR mutation, KRAS mutation and APC mutation were found together in a patient of colon cancer although no clinical significance was reported for their correlation. This case study collectively with our results indicates that KRAS and KDR mutation can together play a role in proliferation of tumor cells when VEGF signaling pathway proceeds via MAPK signaling route.…”
Section: Discussionmentioning
confidence: 99%
“…This difference might be present due to different cancer groups and the small number of patients studied. Furthermore, in a recently reported case study [15], KDR mutation, KRAS mutation and APC mutation were found together in a patient of colon cancer although no clinical significance was reported for their correlation. This case study collectively with our results indicates that KRAS and KDR mutation can together play a role in proliferation of tumor cells when VEGF signaling pathway proceeds via MAPK signaling route.…”
Section: Discussionmentioning
confidence: 99%
“…Because of small sample of Indian patients, response rates cannot be compared with African patients (2 patient's vs. 6 patients). KDR gene mutation occurs in tyrosine kinase domain of VEGFR2 making it a potential target for regoarfenib [2]. Failure of regorafenib in the present study may be due to absence of KDR mutation.…”
Section: Discussionmentioning
confidence: 64%
“…It accounts for over 9% of all cancer incidences [1,2]. Colorectal cancer (CRC) is the third most commonly diagnosed malignancy and the fourth leading cause of cancer-related deaths in the world, and its burden is expected to increase by 60% to more than 2.2 million new cases and 1.1 million cancer deaths by 2030 [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would allow other patients, who are less likely to respond, to avoid the adverse effects of the drug. In this respect, an exceptional response to regorafenib was reported in a patient with metastatic colorectal cancer and a mutation in the KDR gene encoding for VEGFR2 (32). This patient had an ongoing PR for over 9 months at the time of the report, despite being able to tolerate only a reduced dose of 40 mg. Another prolonged PR of 15 months as well as SD for over 20 months were observed in two patients participating in a phase I trial of the combination of regorafenib with cetuximab (33).…”
Section: Discussionmentioning
confidence: 95%